Aplikasi Software AutoCAD Civil 3D dan MDP 2017 dalam Perencanaan Jalan Raya (Studi Kasus: Ruas Jalan Linggarjati – Cirendang Kabupaten Kuningan) - Mira Lestira Hariani; Martinus Agus Sugiyanto; Riyan Septiandri (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
Road infrastructure is a very important sector in regional economic growth. Geometric and flexible pavement planning on Linggarjati - Cirendang road section aims to provide road infrastructure that connects the Promotion Area Activity Center (PKW promotion), Environmental Activity Center (PKL), Regional Service Center (PPK) and Environmental Service Center (PPL) in Kuningan Regency in accordance with the Kuningan Regency Government programs. This research refers to the “Tata Cara Perencanaan Geometrik Jalan Antar Kota Ditjen Bina Marga Tahun 1997”, which was designed using Autocad Civil 3D v.2020 software. For the pavement thickness planning, refer to “Manual Desain Perkerasan Jalan Revisi 2017 Bina Marga”. The planning of the Linggarjati - Cirendang road section result ± 8,260 km long trace with a design speed of 60 km/hour. In the horizontal alignment there are 6 bends, consisting of 2 (two) SCS bends and 4 (four) FC bends. There are a total of 10 points of vertical intersection (PVI) with 6 points of concave PVI and 4 points of convex PVI with a maximum slope of 8%. The need for excavation volume is 217,154.7 m3 and the embankment is 319,259.61 m3. This study resulted in a flexible pavement thickness with a thickness of 30 cm for the base layer, 14.5 cm for AC Base, 6 cm for AC-BC, and 4 cm for AC-WC